Compliance Level of Tax Return Reporting and Tax Revenue: Digital Tax Return Reporting Services, Digital Tax Payment Services and Digital Helpdesk Services - Yudie Fitrianto (Dinasti International Journal of Education Management And Social Science, 2023)
Compliance Level of Tax Return Reporting and Tax Revenue: Digital Tax Return Reporting Services, Digital Tax Payment Services and Digital Helpdesk Services Services are scientific literature study articles within the scope of economics. The purpose of this article is to build a hypothesis of the role between variables that will be used in future research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. Risearch library method method, from e-book and open access e-journal. The results of this article are: 1) digital tax return reporting services play a role in the level of compliance with tax return reporting and tax revenue; 2) digital tax payment services play a role in the level of compliance with tax return reporting and tax revenue; and 3) digital helpdesk services play a role in the level of compliance with tax return reporting and tax revenue.